Seborrheic Pemphigoid. (18th August 2014) - Errichetti, Enzo; Stinco, Giuseppe; Pegolo, Enrico; di Meo, Nicola; Trevisan, Giusto; Patrone, Pasquale
Abstract : Seborrheic pemphigoid (SP), first described in 1969 by Schnyder, is a peculiar variant of BP which clinically resembles pemphigus erythematosus, since it is characterized by ruptured bullae and erosions covered with crusts involving the seborrheic areas. To the best of our knowledge, from the first description only four other cases of SP have been reported, of which two are in the English literature. We report an additional case of SP in a 56-year-old man with cervical spondylogenic myelopathy with very impaired mobility.